Academic Staff Direct Participation in Managing Higher Education Institutions - Pilot Study Report = Partycypacja bezpośrednia nauczycieli akademickich w zarządzaniu uczelnią - komunikat z badania pilotażowego - Szelągowska-Rudzka, Katarzyna (Zielona Góra: Faculty of Economics and Management Press)
The aim of the study is to present the results of pilot study on academic staff direct participation (ASDP) in managing higher education institutions (HEI) (content, scope, intensity, practicality of impact), in key areas of its activity and its advantages and risks. The research was carried out under questionnaire survey method among academic staff of selected HEIs, in autumn 2018.
Keywords: zarządzanie uczelnią; kadra akademicka; partycypacja bezpośrednia nauczycieli akademickich; PBNA; formy partycypacji; korzyści z PBNA; zagrożenia związane z PBNA; university management; academic staff; academic staff direct participation; ASDP; forms of direct participation; advantages of ASDP; disadvantages of ASDP